The Role of the FMN-Domain of Human Cytochrome P450 Oxidoreductase in Its Promiscuous Interactions With Structurally Diverse Redox Partners - Esteves, Francisco; Campelo, Diana; Gomes, Bruno Costa; Urban, Philippe; Bozonnet, Sophie; Lautier, Thomas; Rueff, José; Truan, Gilles; Kranendonk, Michel (Frontiers in Pharmacology, 2020)
NADPH cytochrome P450 oxidoreductase (CPR) is the obligatory electron supplier in sustaining activity of microsomal cytochrome P450 (CYP). The variant nature of the isoform specific proximal interface of microsomal CYPs implies that CPR is capable of multiple degenerated interactions with CYPs for electron transfer, through different binding mechanisms, which are still not well understood. Recently, we showed that CPR dynamics allows the formation of open conformers that can be sampled by its structurally diverse redox partners in a CYP-isoform dependent manner. To further investigate the role of the CPR FMN-domain in effective binding of CPR to its diverse acceptors and clarify the underlying molecular mechanisms, five different CPR-FMN-domain random mutant libraries were created. These libraries were screened for mutants with increased activity when combined with specific CYP-isoforms. Seven CPR-FMN-domain mutants were identified, supporting a gain in activity for CYP1A2 (P117H, G144C, A229T), 2A6 (P117/L125V, G175D, H183Y) or 3A4 (N151D). Effects were evaluated using extended enzyme kinetic analysis, cytochrome b5 competition, ionic strength effect on CYP activity, and structural analysis. Mutated residues were located in or adjacent to several acidic amino acid stretches, formerly indicated to be involved in CPR:CYP interaction, or close to two tyrosine residues suggested to be involved in FMN binding. Several identified positions co-localize with mutations found in naturally occurring CPR variants, previously shown to cause CYP-isoform-dependent effects. The mutations do not seem to change considerably the geometry of the FMN-domain, but are likely to cause very subtle alterations leading to improved interaction with a specific CYP. Overall, CYPs seem to interact with CPR using an isoform specific combination of several binding motifs of the FMN-domain.